Enhanced Electrochemical Capability of LiNi1/3Co1/3Mn1/3O2 Cathode Materials Coated with Fluoroborate Glass for Lithium‐Ion Batteries. Issue 5 (27th February 2017) - Zhang, Qibing; Wang, Lei; Zhu, Chunhua; Sun, Zhipeng; Cheng, Wenhua; Lv, Dingding; Ren, Wei; Bian, Liang; Xu, Jinbao; Chang, Aimin
Abstract: A LiNi1/3 Co1/3 Mn1/3 O2 (NCM) cathode material is coated with fluoroborate glass ( x Li2 O‐ y B2 O3 ‐ z LiF) to improve the electrochemical performance of lithium‐ion batteries. An x Li2 O‐ y B2 O3 ‐ z LiF layer was successfully coated onto the surface of NCM by using a solution‐phase method. The resulting materials are characterized by using X‐ray diffraction, scanning electron microscopy, and transmission electron microscopy. The x Li2 O‐ y B2 O3 ‐ z LiF‐coated NCM exhibits a superior discharge capacity, rate capability, and cycling stability than those of the uncoated material. Notably, the initial discharge capacity of bare and 2Li2 O‐B2 O3 ‐LiF‐coated NCM were 182.1 and 207.5 mAhg −1, respectively, in the voltage range from 2.5 to 4.5 V. At a rate of 5C, the discharge capacity of Li2 O‐B2 O3 ‐LiF‐coated NCM is 144.4 mAhg −1, whereas that of bare NCM is 76.7 mAhg −1 . After 50 cycles at a rate of 0.2C, the capacity retentions of Li2 O‐B2 O3 ‐LiF‐, 2Li2 O‐B2 O3 ‐LiF‐, Li2 O‐2B2 O3 ‐LiF‐, and Li2 O‐B2 O3 ‐2LiF‐coated NCM are 96.8, 97.2, 95.6, and 95.2%, respectively, whereas the capacity retention of bare NCM is 81.4%. Cyclic voltammetry and electrochemical impedance spectroscopy results indicate that the x Li2 O‐ y B2 O3 ‐ z LiF coating reduces electrode polarization and decreases charge‐transfer resistance at the electrolyte–electrode interface, further improving the electrochemical activity of the NCM cathode material. Abstract : The core of the matter : An x Li2 O‐ y B2 O3 ‐ z LiF layer is successfully coated onto the surface of LiNi1/3 Co1/3 Mn1/3 O2 (NCM) by using a solution‐phase method. The x Li2 O‐ y B2 O3 ‐ z LiF‐coated NCM exhibits a superior discharge capacity, rate capability, and cycling stability compared to those of the uncoated material.